COVID-19 pandemic wave: A global struggle and ways to control - Singh, Asem Surindro; Takhellambam, Machathoibi Chanu (Archives of Community Medicine and Public Health, 2020)
COVID-19 is currently world’s most dangerous disease. According to the latest worldometer data, COVID-19 has infected almost 22 million people living across the world, since its outbreak in January 2020. Out of the 22 million, 0.77 million had died and over 14 million have recovered; and more than 64 thousands of people are living at critical condition. It has greatly affected normal lives of the people, free movement, social interaction, education, business and many more. Every nation is paying full attention on fight against the disease. This review is a brief highlight on this current issue and discuss on how we can overcome this raging transmission of COVID-19.